Unethical behavior under relative performance evaluation: Evidence and remedy - Tzini, Konstantina; Jain, Kriti (Human Resource Management, 2018)
Relative performance evaluation, wherein the performance of employees is evaluated relative to the performance of their peers, is popular within organizations. In this article, we report four experimental studies to explore the impact that such an evaluation system has on unethical behavior. We find that participants under relative performance evaluation expect others to be more likely to use unethical means (Study 1) and indulge more in unethical behavior themselves (Study 2). Drawing on these results, in Study 3 we propose a technique that we call consequential reflection to reduce intentions of unethical behavior, and we also test for the mediating role of perceived risks and benefits. In Study 4, we explore how individual differences in rational–intuitive decision‐making styles moderate the effectiveness of consequential reflection. Overall, the article provides evidence of moral side effects of relative performance evaluation. Furthermore, keeping in mind the constraints and needs of practitioners, we suggest a simple intervention to curb tendencies toward unethical behavior.